K-ras mutations and cell kinetics in Helicobacter pylori associated gastric intestinal metaplasia: a comparison before and after eradication in patients with chronic gastritis and gastric cancer. Issue 8 (22nd September 2006) - Watari, J; Tanaka, A; Tanabe, H; Sato, R; Moriichi, K; Zaky, A; Okamoto, K; Maemoto, A; Fujiya, M; Ashida, T; Das, K M; Kohgo, Y
Abstract : Background: Helicobacter pylori related gastric intestinal metaplasia (IM) is considered to be a precancerous lesion. Aims: To identify the effects of H pylori eradication on K- ras mutations, cell kinetics in IM and histological changes in patients with and without gastric cancers in a one-year prospective study. Methods: Patients included group A (n = 39), chronic gastritis, and group B (n = 53), intestinal-type early gastric cancer patients who had all undergone endoscopic mucosal resection (n = 25) or surgical resection (n = 28). K- ras codon 12 mutations in IM were examined, followed by DNA sequencing analysis. Proliferating and apoptotic cells were detected with anti-Ki-67 antibody and using the TUNEL method, respectively. Results: The incidence of K- ras mutations in the cancer was only 3.8%. The mutant K- ras in IM was observed more frequently in group A (46.2%) than in group B patients (1.9%) (p<0.005). After eradication, the K- ras mutations significantly declined to 12.8% in group A (p<0.005). The mutation pattern of K- ras codon 12 before eradication was that GGT was mainly changed to AGT (50%) in group A. AGT transformation was not affected by treatment. Apoptosis in IM showed an increase after H pylori eradication in both groups (p<0.05 in group A) although no histological improvement in IM was observed. The monocyte score was significantly higher in group A than in group B (p<0.05); the score improved significantly after eradication. Conclusions: K- ras mutations in IM do not always play a role in gastric carcinogenesis but cell kinetics, especially apoptosis, in IM may contribute to it. There are early events in K- ras mutations which are influenced by H pylori infection; some mutations may also be selected by eradication. These unstable K- ras mutations in IM may be related to lymphocyte infiltration caused by H pylori infection.